2014
DOI: 10.1590/s0100-72032014000300004
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal abnormalities in couples with recurrent first trimester abortions

Abstract: An association between chromosomal abnormalities and recurrent miscarriage in the first trimester of pregnancy (OR=7.7; 95%CI 1.2--170.5) was observed in the present study. Etiologic identification of genetic factors represents important clinical information for genetic counseling and orientation of the couple about the risk for future pregnancies and decreases the number of investigations needed to elucidate the possible causes of miscarriages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 17 publications
4
17
2
2
Order By: Relevance
“…The frequency of chromosomal abnormalities was found to be higher in women with recurrent miscarriages (7.3%) than in men (2.1%) (Gonçalves et al, 2014). A proposed mechanism contributing to the higher incidence of female translocation carriers is that only one ovum matures each month, whereas male carriers release millions of sperm in every ejaculation, resulting in possible pre-zygotic selection against unbalanced gametes (Kochhar and Ghosh, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of chromosomal abnormalities was found to be higher in women with recurrent miscarriages (7.3%) than in men (2.1%) (Gonçalves et al, 2014). A proposed mechanism contributing to the higher incidence of female translocation carriers is that only one ovum matures each month, whereas male carriers release millions of sperm in every ejaculation, resulting in possible pre-zygotic selection against unbalanced gametes (Kochhar and Ghosh, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent spontaneous abortions (RSAs) occur in approximately 15-20% of all clinically recognizable pregnancies (Dutta et al, 2011;Gada Saxena et al, 2012;Turki et al, 2014;Ghazaey et al, 2015). RSA is considered a multifactorial problem, with different causes involved in its etiology, including genetic, environmental, endocrine, and infectious diseases (Gonçalves et al, 2014). Parental chromosomal abnormalities are an important genetic cause of RSAs and recurrent miscarriage (Rubio et al, 2003;Pourjafari et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Based on our present and previous results [23], we presume that at least two different subgroups of patients with X chromosome mosaicism exist. The mean age of women with true X mosaicism and low-level X mosaicism was significantly different in both studies; in our recent study, the values were In couples with recurrent spontaneous abortion, X chromosome mosaicism was identified in 3-16% [33,[35][36][37][38][39]. In 50 cells counted, Düzcan et al showed mosaicism of either structural rearrangements or aneuploidies of sex chromosomes in 7 cases out of 354 with reproductive failure [38].…”
Section: Discussionmentioning
confidence: 63%
“…The case group was comprised 137 women with an obstetrical history of two or more consecutive first-trimester abortions (£12 weeks gestation). Inclusion and exclusion criteria were consistent with those defined in a previous study conducted by our group (Gonçalves et al, 2014). The control group consisted of 100 healthy women with no history of pregnancy loss, with at least one living child, and ≤40 years of age.…”
Section: Study Subjectsmentioning
confidence: 99%